A radiological evaluation of the morphometry and safety of S1, S2 and S2-ilium screws in the Asian population using three dimensional computed tomography scan: an analysis of 180 pelvis - Kwan, M.K.; Jeffry, A.; Chan, C.Y.W.; Saw, L.B. (2012)
Studies of sacral pedicle anatomy have been reported in the European population. However, the feasibility for the use of S1, S2 and S2-ilium screws has not been fully investigated in the Asian population. To assess feasibility, morphometric parameters and safety of S1, S2 and S2-ilium screw insertion in the Asian population. 180 three dimensional computed tomography (CT) scans of pelvis (90 males and 90 females) with contrast were analysed using Mimics(A (R)) version 13.1 (Materialise, Belgium) software. All parameters were measured using this programme. The safety medial trajectory of S1 pedicle screw was 11.8 +/- A 3.9 to 37.1 +/- A 4.5A degrees in males and 11.7 +/- A 3.1 to 35.9 +/- A 4.4A degrees in females. The screw length was from 35.0 +/- A 3.0 to 58.3 +/- A 3.1 mm in males and from 31.9 +/- A 2.6 to 53.1 +/- A 3.5 mm in females. Right S1 pedicle screws were safe as long as the anterior cortical penetration of quadrant 2, 3 and 4 were avoided. On the left, it was safe for the screws to exit at quadrant 1, 2 and 3. The lateral trajectory of S2 sacral alar screw was from 0 to 32.6 +/- A 3.3A degrees in males and from 0 to 33.6 +/- A 3.5A degrees in females. The screw length was from 23.9 +/- A 3.2 to 53.1 +/- A 4.1 mm in males and from 23.0 +/- A 2.5 to 53.2 +/- A 4.5 mm in females. For S2 screws, on the right side, the frequency of the internal iliac artery location was 7.2, 38.3, 47.2 and 1.7 for quadrants 1, 2, 3 and 4, whereas on the left side, the frequency was 7.8, 50.6, 33.9 and 2.2 for quadrants 1, 2, 3 and 4. For S2-ilium screws, the lateral trajectory was from 39.3 +/- A 3.1 to 50.4 +/- A 6.1A degrees in males and from 39.5 +/- A 3.1 to 50.2 +/- A 5.9A degrees in females. The screw lengths were from 85.3 +/- A 22.2 to 122.6 +/- A 11.4 mm and from 86.4 +/- A 22.7 to 122.2 +/- A 11.9 mm in males and females, respectively. The application of S1, S2 and S2-ilium screws are feasible. The amount of medial angulation and the ideal screw length in the Asian population must be borne in mind during insertion. Right S1 screws carry higher risk of injury to the internal iliac artery when the anterior cortical penetration occurs due to the course of the iliac vessels.